Hubungan konsumsi zat besi dan pola menstruasi dengan kejadian anemia pada remaja putri di SMAN 1 Glumpang Tiga Kabupaten Pidie - Jeny Riska Vatica; Desi Murdiatama; Kasrawati Kasrawati (Nur Science Institute, 2025)
Adolescent girls are estimated to have a tenfold higher risk of anemia than adolescent boys. This is largely because they experience monthly menstruation and are in a growth period, which increases their iron requirements. This study aimed to examine the associations among iron consumption, menstrual patterns, and the incidence of anemia among adolescent girls at SMAN 1 Glumpang Tiga, Pidie Regency. An analytical cross-sectional design was used, and data were collected from July 22–24, 2025. A total of 63 adolescent girls were selected using random sampling. Data were gathered through questionnaires and analysed using the chi-square test. The findings indicated that iron consumption and menstrual patterns were significantly associated with anemia among adolescent girls. Therefore, adolescent girls are encouraged to seek early health screening when signs and symptoms of anemia are identified, so that healthcare professionals can provide appropriate management.